Resenha do livro "How to Run the World: Charting a Course to the next Renaissance”, de Parag Khanna - Stuenkel, Oliver (Meridiano 47 - Journal of Global Studies, 2017)
In his new book, Parag Khanna, Director of the Global Governance Initiative at the New America Foundation and author of “The Second World”, seeks to answer how we can deal with global challenges in a more effective way in the years to come. In merely 214 pages, Khanna covers a vast array of challenges ”“ from climate change, nuclear proliferation, poverty, human rights to the Middle East Conflict to the disputes in Kashmir, Iran and Afghanistan. As a natural consequence, some of his analyses seem a bit rushed (for example, his thoughts on nuclear proliferation are limited to just a few pages). Yet Khanna’s aim is not to engage in profound historical analysis; rather, the book can be understood as a smart brainstorming session on how to tackle the world’s most urgent problems. Academics will frown at his approach as Khanna’s assertions are not based on empirical research, yet he is certainly courageous for approaching big issues in a sweeping way.